Six weeks of lower limb exercise on pain, quality of life and muscle fatigue in women with gestational varicose veins - Fatemeh Mallah; Mina Zeinalzadeh; Dara Alvandfar (Mashhad University of Medical Sciences, 2021)
Introduction: Following the high prevalence of gestational varicose veins and considering that lower limb exercises in pregnant women can be performed at home and doing such non-pharmacological interventions does not require special expertise, this study was performed with aim to evaluate six weeks of exercise on lower limb pain, quality of life and muscle fatigue in women with gestational varicose veins. Methods: This randomized controlled clinical trial study was performed in 2019 on 24 pregnant women with gestational varicose veins referred to Alzahra Hospital in Tabriz. After randomly assigning participants in two groups of 12 subjects, the intervention group performed lower extremity exercises five times a day for six weeks. Pain intensity, muscle fatigue and quality of life in varicose veins were measured before and after the intervention. Data were analyzed by SPSS software (version 22) and dependent and independent t-test. P<0.05 was considered statistically significant.   Results: The pain intensity, quality of life and muscle pain showed statistically significant difference between these variables before the intervention (P>0.05), while the intragroup study of the results in the intervention group showed that pain intensity (P=0.001), quality of life (P=0.009) and muscle fatigue (P=0.005) were significantly associated with a decrease at the end of the intervention. On the other hand, the intergroup comparison showed that pain intensity (P=0.005), quality of life (P=0.001) and muscle fatigue (P=0.001) significantly reduced at the end of the intervention. Conclusion: Six weeks of exercise program reduced pain intensity, muscle fatigue and increased quality of life in women with gestational varicose veins.